A STUDY ON CUSTOMER SATISFACTION TOWARDS SBI YONOWITH SPECIAL REFERENCE TO KOLLAM DISTRICT - Gopal R, andana; V S, Akshaya; A, Arjun; A, Abymon (International Journal of Psychosocial Rehabilitation, 2020)
Mobile phones and their various technologies has become an inevitable part of people all over the world. Due to the drastic change in technologies and day to day innovations in mobile phones, software developers of mobile phones are coming with new ideas that are making the life of people smoother and easier. One of the major industries that have benefited from mobile technology is the Banking Industry. This technology / digitalization has played an important role in promoting this sector very well. Mobile banking in India is expanding briskly because customers find it a more easy, congenial and acceptable way of doing banking transactions. STATE BANK OF INDIA (SBI) is one of the biggest commercial banks in India and is among the colossal retail bank in the world. In addition to this it has become a dominant player in digital place. It has always been at the forefront of Digital Banking innovations. SBI YONO (YOU ONLY NEED ONE) is one example of that. SBI YONO is a consolidated digital banking platform provided by SBI. This platform allows the customers of SBI to access a variety of monetary (financial) and other services. This article is an effort to study the satisfaction level of customers towards the SBI YONO application.